DEGRADASI AGRARIS SEBAGAI IDE PENCIPTAAN FURNITURE CAFE - Prasetiyo Yunianto (Corak : Jurnal Seni Kriya, 2014)
The creation of this art work is based on the response to the agrarian degradationphenomenon in Indonesia, in the case of the decrease of the farmer number and the field area,and the modernity pressure problem among the farmers. The material used on this work iswood and metal which are created by welding and working seat technique with finishing wax.This art work is created to be functional furniture by using furniture café as the object to deliverthe message and critic trough the concept of agrarian degradation phenomenon in Indonesia.The target audience of this art work is young college students. This art work creation isexpected to be able to wake the people’s awareness toward the agrarian degradation occurs inthe society and the young generation as the agent of change is hopefully can respond thephenomenon positively.Keyword : Agrarian, degradation, idea, furniture, cafe  Penciptaan karya ini berlatar atas respon terhadap fenomena degradasi agraris diIndonesia, berkurangnya jumlah petani dan lahan tanam serta permasalahan himpitanmodernitas dikalangan masyarakat petani. Material yang digunakan adalah kayu dan logam,menggunakan teknik welding dan teknik kerja bangku, dengan finishing wax. Tujuan daripenciptaan karya ini berfungsi sebagai furniture murni dan juga menciptakan karya senidengan menggunakan furniture cafe sebagai objek karya penyampai pesan, kritik dengankonsep fenomena degradasi agraris di Indonesia. Target audience dari penciptaan karya iniadalah masyarakat muda mahasiswa. Dari penciptaan karya ini diharapkan mampumenggugah kesadaran masyarakat atas fenomena degradasi agraris yang terjadidimasyarakat , sehingga masyarakat muda sebagai agen perubahan dapat menyikapinyadengan respon positif.Kata kunci : degradasi, agraris,ide, furniture, cafe